Reducing the Risks for Substance Abuse A Lifespan Approach - Daugherty, Raymond P.; Leukefeld, Carl (Springer US, 1998)
Authors Raymond P. Daugherty and Carl Leukefeld argue for replacing the youth-based, 'zero tolerance' approach to substance abuse prevention that has been dominant in the field over the past two decades. Their dynamic alternative is the Lifestyle Risk Reduction Model, which revises standard prevention strategies to make them relevant throughout the entire life span. Features of this revolutionary new paradigm include Five Principles of Lifestyle Risk Reduction (LRR), Five Conditions of Effective LRR, and the LLR Formulas
Keywords: Public Health; Health Promotion and Disease Prevention; Medicine; Drogenabhängigkeit; Lebensalter; Alkoholismus; Gesundheitsvorsorge; USA